Lightweight and high-security laser-based cotton tip pruning robot - Guo, Xuanang; Mao, Ziyang; Shi, Zedong; Lu, Wei (International Journal of Agricultural and Biological Engineering, 2024)
Considering the current environmental pollution caused by chemical topping, plant damage caused by mechanical topping, and the high cost of manual topping, a laser-based cotton-tip pruning robot for field cotton was designed in this study. The main advantages of this robot include its safety, light weight, low cost, and environmental friendliness. First, the structural design, measurement, and corresponding control system design of the robot were realized. Subsequently, a precise laser control method based on Yolov5 cotton top identification and the inverse kinematic solution of parallel robot rapid positioning were examined. Subsequently, the optimal laser irradiation wavelength and duration were determined. Finally, a laser-topping experiment was conducted, and the overall accuracy and recall rates for cotton identification were 98.3% and 99.3%, respectively. The AP and mAP at the threshold value of 0.5 reached 99.3% and 78.8%, respectively. The maximum positioning error of the jacking system is 2.6 mm, and the repeated positioning error is within ±1.2 cm, which meets the accuracy requirements of laser jacking. Blue-purple laser irradiation at 15 W and 405 nm for 22 s was the best topping scheme. Comparing the effects of cotton topping with and without manual topping, it can be seen that laser topping significantly improved the yield and quality. Combined with the photothermal response of the cotton topping, the feasibility of laser topping was verified both theoretically and experimentally. The laser-topping scheme proposed in this study exhibits high efficiency, environmental protection, and safety, as well as good application prospects. Key words: laser topping; parallel manipulator; photothermal response; object detection DOI: 10.25165/j.ijabe.20241704.8385 Citation: Guo X A, Mao Z Y, Shi Z D, Lu W. Lightweight and high-security laser-based cotton tip pruning robot. Int J Agric& Biol Eng, 2024; 17(4): 98–108